Innovation and Productivity in the Malaysian Food Processing Industry: An Empirical Analysis using a System Generalised Method of Moments Approach - Kamal, Sarah Nursyazmin Mohamad; Ismail, Normaz Wana; Sidique, Shaufique Fahmi Ahmad (Asian Journal of Empirical Research, 2022)
The food processing industry was reviewed as a top priority for industrial development and targeted to lead greater growth in Malaysia’s Industrial Masterplan (NIMP). Leading to industrial development, this paper highlighted the relationship between innovative activities (R&D expenditure and ICT expenditure) and productivity with other variables like the presence of skill intensity, capital intensity, export intensity, foreign-owned firms and imported intermediate input. This hypothesis is examined for a panel dataset of the food processing industry in Malaysia from 2000 until 2015 (according to Economic Census- Manufacturing). Using a System Generalised Method of Moments (GMM) approach, empirical analysis suggests that innovators performed better than non-innovators in terms of labour productivity. Innovative activity and ICT expenditure along with skilled intensity and capital intensity seem to be the main determinants of subsector’s productivity, whereas R&D expenditure has mixed results from the estimation output.